The Effect of Resistance Training on Quality of Life and Hormonal Balance in Menopausal Women - Nikel Ramadhan; Muhammad Hilal Lazuardi; Nazwa Tri Adha; M. Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
Menopause is a physiological phase characterized by a decline in estrogen levels, which affects women's quality of life and hormonal balance. This condition often triggers physical and psychological disturbances, along with an increased risk of degenerative diseases. One potential non-pharmacological intervention is resistance training, which has been shown to improve muscular strength and modulate hormonal responses. This study aimed to analyze the effect of resistance training on quality of life and hormonal balance in menopausal women. The research method used a quasi-experimental design with a pre-test and post-test control group approach. The sample consisted of 20 menopausal women divided into experimental and control groups. The experimental group participated in a resistance training program for 12 weeks with a frequency of three sessions per week. The instruments used included the Menopause-Specific Quality of Life (MENQOL) questionnaire and laboratory analysis of estradiol (E2) and Follicle Stimulating Hormone (FSH) levels. Data were analyzed using paired sample t-tests and independent sample t-tests with a significance level of 0.05. The results showed a significant improvement in quality of life and estradiol levels, as well as a reduction in FSH levels in the experimental group (p < 0.05), while the control group showed no significant changes. These findings indicate that resistance training is effective in improving physical and psychological well-being while stabilizing hormonal balance. Overall, it can be concluded that resistance training is an effective intervention that can be recommended to improve quality of life and hormonal balance in menopausal women.